24.4: A Linear High‐Tg Arylphosphine Oxide‐Triazine Conjugate as a Doped Electron‐Transport Material for Stable Phosphorescent OLEDs. (26th August 2021) - Wang, Lin-Ye; Chen, Ling-Ling; Huang, Xiao-Lan; Wang, Mei; Zhu, Xu-Hui; Zou, Jian-Hua
Abstract : Organic electron‐transport materials (ETMs) play a critical role in enhancing performances and operational stability of organic light‐emitting diodes. In this context, we describe a triazine‐based electron‐transport material in high purity 6‐dphenylphosphinyl‐6′‐(4, 6‐(tiphenyl‐1, 3, 5‐triazin‐2‐yl)[2, 2′‐binaphthyl] (DPO‐2Na‐TRZ, MW= 685.75) via arylphosphine oxide modification. It exhibits a glass transition temperature of 130.8 °C. HOMO = −6.03 eV, LUMO = −3.08 eV. Its decomposition occurs at ca. 456 °C at 1% weight loss. Upon 50 wt% Liq doping, DPO‐2Na‐TRZ is investigated as an electron transport layer in bottom‐ and top‐emission green phosphorescent OLEDs. In the presence of an additional exciton‐blocking/electron‐transport layer, the resulting topemission OLED provides attractive characteristics. At a luminance of ca 1000 cd m −2, LE = 91.6 cd A −1, PE = 102.8 lm W −1 and EQE = 22.1 %. Moreover, under continuous driven at a constant current, an extraordinary lifetime t99 > 600 h @ 1000 cd m −2 is observed.